2021
DOI: 10.5435/jaaos-d-20-01092
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Management of Partial Thickness Rotator Cuff Tears: A Comprehensive Review

Abstract: Partial thickness rotator cuff tears (PRCTs) are a challenging disease entity. Optimal management of PRCTs continues to be controversial. Although advances in magnetic resonance imaging and ultrasonography have aided in early diagnosis, arthroscopic evaluation remains the benchmark for diagnosis. Conservative treatment is often the first line of management for most patients; however, evidence suggests that surgical intervention may limit tear progression and the long-term sequelae. Surgical decision making is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 52 publications
0
29
0
Order By: Relevance
“…During the healing process of tendons, the infiltration of inflammatory cells leads to edema. In the fat suppression image of the T2 sequence of MRI scans, the inflammatory edema appears bright white, whereas collagen fibers of the normal tendon appear dark black [26,[31][32][33]. In this study, the MRI results in the micropattern SF film group showed a continuous black stripe signal after 8 months of repair, and the intensity was highest among all experimental groups, indicating that the micropattern SF films performed better in tendon reconstruction.…”
Section: Discussionmentioning
confidence: 48%
“…During the healing process of tendons, the infiltration of inflammatory cells leads to edema. In the fat suppression image of the T2 sequence of MRI scans, the inflammatory edema appears bright white, whereas collagen fibers of the normal tendon appear dark black [26,[31][32][33]. In this study, the MRI results in the micropattern SF film group showed a continuous black stripe signal after 8 months of repair, and the intensity was highest among all experimental groups, indicating that the micropattern SF films performed better in tendon reconstruction.…”
Section: Discussionmentioning
confidence: 48%
“…9 From the 1990s until now, a great advance has taken place in the surgical techniques for the treatment of PTRCTS. 10 , 11 , 12 The surgical approach has evolved from open to arthroscopic surgery. In addition, the surgical technique has evolved from simple debridement to repair after completion and transtendon repair.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the location of impingement mostly occurs in the lateral rotator cuff although this can occasionally occur in a medial position (close to the tendon‐muscle interface) 11 . The shape of rotator cuff injury caused by impingement does not always present with the same morphology 12 . However, our own clinical observations suggest that this can be divided into four types: horizontal tears, longitudinal tears, L‐shaped tears, and irregular tears.…”
Section: Introductionmentioning
confidence: 90%